Induction of fertile oestrus in ewes by administration of prostagladin (F2a) a month before the begining of the breeding season - ΤΣΑΜΗΣ, Κ.; ΠΟΙΛΑΣ, Σ. (Journal of the Hellenic Veterinary Medical Society, 2019)
In order to induce oestrus in ewes by administration of PGF2a a month before the beginig of breeding season we used the product LUTALYSE of UP-JOHN in dose of 15 mg per ewe The ewes were hybrids between Mytilene and East Friesian in good nutritional and hygienic state and aged 2-7 years old. The breeding season for the last 3-4 years used to begin the last days of June. Before starting the experiment we introduced teaser rams in the herd which remained for 8 days without being noticed any sign of oestrus. We injected PGF2o in 66 ewes on 8th of June 1978. From these 39 (59,09%) showed oestrus and inseminated artificially twice. Thirty three (84,61%) ewes showed oestrus until 48 hours, 4 (10,25%) ewes until 72 hours and 2 (5,12%) until 96 hours. In 16 control ewew no sing of oestrus was appeared. From 39 ewes, that inseminated artificially, lambed 32 (82%). The productivity in the experimental group was 48,48% (32/66) while in the control group was 0 (0/16) in the corresponding period. Those ewes that did not appear oestrus and those that did not inseminate showed oestrus after 20 days. The second oestrus coincide with the begining of oestrus in the control group.